DEVELOPMENT OF A COMMUNITY – BASED EDUCATION (CBE) MODEL IN THE ISLAMIC BOARDING SCHOOL EDUCATION SYSTEM - Wahid, Abdul; Zamroni, Zamroni; Tamam, Badrut; Gumilang, Randi Muhammad (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Education plays a crucial role in human resource development. There is community participation that is needed in order to encourage acceleration in order to achieve maximum and sustainable results. Islamic boarding schools are educational institutions that throughout their history have always been close and connected to society. This is a social fact at the Mambaul Ulum Islamic Boarding School, East Kutai. Islamic boarding school that was born in the culture and traditions of Nahdlatul Ulama (NU), and grew amidst a heterogeneous urban-industrial society. It is worthy of being studied in various actual dimensions related to the various opportunities and challenges in the process of implementing a form of community-based education or Community-Based Education (CBE) at the Mambaul Ulum Islamic Boarding School, East Kutai. This research uses a case study method, through in-depth interviews and field observations. So it is hoped that we can understand the phenomena that exist in the implementation and development of the Community-Based Education (CBE) model at the Mambaul Ulum Islamic Boarding School, East Kutai. In-depth data mining involved Islamic boarding school leaders, teachers, students and the community/collaboration partners. Observations on various activities and facility sites in Islamic boarding schools are needed to obtain confirmatory validity of the various data needed. Research findings show that CBE can improve the quality of Islamic boarding school education. Active participation in various socio-religious dimensions, a strong collaborative network for guidance and support for facilities, as well as the integration of religious competence with social-religious skills are indications of improving quality. Supporting factors for implementing CBE include visionary leadership from kiai, supportive social and geographical construction, as well as community trust and acceptance. However, there are obstacles in the form of competition between Islamic boarding schools in relatively narrow areas and Islamic boarding school identities that limit segmentation. Overall, the implementation of CBE shows great potential in improving the quality of education and community empowerment at the Mambaul Ulum Islamic Boarding School, East Kutai.